Analysis of the embedded convection of frontal cloud systems based on satellite and ground-based measurements - Zhukov, Denis F. (Proceedings of SPIE)
Based on satellite and ground-based measurements, the characteristics of the atmosphere during the passage of frontal cloud systems with embedded convection were evaluated. An approach was developed to identify centers of embedded convection in frontal cloud systems, which allows one to identify with high probability mesoscale phenomena in frontal clouds (in the horizontal and vertical planes). Based on the developed approaches and the obtained estimates of atmospheric characteristics, the methodology of automatic detection of the centers of embedded convection using satellite data will be implemented.